Activating both Halogen and Chalcogen Bonding Interactions in Cation Radical Salts of Iodinated Tetrathiafulavalene Derivatives. Issue 9 (28th August 2020) - Beau, Maxime; Jeannin, Olivier; Lee, Sunhee; Barrière, Frédéric; Fourmigué, Marc; Jeon, Ie‐Rang
Abstract: Halogen bonding (XB) interactions are investigated in cation radical salts of bis(methylthio)‐5, 5'‐diiodotetrathiafulvalene (1 ). Electrocrystallization of 1 in the presence of Bu4 NCl affords a 1 : 1 salt formulated as ( E ‐1 )Cl. Particularly strong I⋅⋅⋅Cl − XB interactions are observed around the Cl − anion with the distances at 78 % the sum of the van der Waals radii, a consequence of the XB charge activation in the cation radical. Moreover, the Cl − environment is complemented by two extra S⋅⋅⋅Cl − chalcogen bonding (ChB) interactions, an original feature among reported halide salts of TTF derivatives. Electrostatic potential calculations on the cation radical further demonstrate the efficient activation of the S atoms of the 1, 3‐dithiole rings (Vs, max =87.2 kcal/mol), as strong as with the iodine atoms (Vs, max =87.9 kcal/mol). The radical cations form weakly dimerized stacks, as confirmed by the variable‐temperature magnetic susceptibility and the weak conductivity (4.8×10 −5  S cm −1 ). Abstract : Two in one : Strong and simultaneous halogen (XB) and chalcogen (ChB) bonding interactions are identified in the 1 : 1 salt of a diiodotetrathiafulvalene cation with Cl − anion. Electrostatic potential calculations on the cation radical further demonstrate the efficient activation of the sulfur atoms of the 1, 3‐dithiole rings, as strong as with the iodine atoms. The radical cations form weakly dimerized stacks, as confirmed by the variable‐temperature magnetic susceptibility and the weak conductivity.